An assessment of the contribution of food aid programs to household food security of smallholder farmers in Buhera District, Zimbabwe - Tinarwo, Christina (Midlands State university, 2015)
The study was carried out in Buhera District in 2013. The aim of the study was to assess the contribution of food aid on food security. The study sampled 30 households using simple random sampling who are the beneficiaries of food aid. Food aid programme is widely debated in the world and has made many people to believe that food aid has a disincentive effect while others believe it is an essential tool for agriculture and food security development. For the past decade, food aid deliveries have featured Buhera district following its food deficit. The primary data was collected using a questionnaire and was analysed using descriptive statistics, mean comparison, and ordinary least squares using STATA software package. The results shows that the number of cattle owned by a household and food aid deliveries were statistically significant and contribute to food security of the smallholder farmers. Off-farm activities and area planted were statistically insignificant but they have a contribution to the household food security. Finally household size and sex of the household head had an inverse relationship with household food security. The study recommend that off-farm employment should be persued and development of irrigation schemes so as to improve the small-holder farmers food security.